2007
DOI: 10.1007/s11103-007-9204-5
|View full text |Cite
|
Sign up to set email alerts
|

The HvNAC6 transcription factor: a positive regulator of penetration resistance in barley and Arabidopsis

Abstract: Pathogens induce the expression of many genes encoding plant transcription factors, though specific knowledge of the biological function of individual transcription factors remains scarce. NAC transcription factors are encoded in plants by a gene family with proposed functions in both abiotic and biotic stress adaptation, as well as in developmental processes. In this paper, we provide convincing evidence that a barley NAC transcription factor has a direct role in regulating basal defence. The gene transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 74 publications
2
111
0
Order By: Relevance
“…Previous studies showed that plant NAC genes were implicated in responses to abiotic and biotic stimuli (e.g., Delessert et al, 2005;Jensen et al, 2007;Kim et al, 2007;Lin et al, 2007;Lu et al, 2007). Our analysis of the expression of MmATAF1 and MmNAP genes in shoots showed that they were also induced by mechanical wounding, ZnSO 4 , abscisic acid, and salicylic acid treatments with variable expression levels ( Figure 7B-E).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies showed that plant NAC genes were implicated in responses to abiotic and biotic stimuli (e.g., Delessert et al, 2005;Jensen et al, 2007;Kim et al, 2007;Lin et al, 2007;Lu et al, 2007). Our analysis of the expression of MmATAF1 and MmNAP genes in shoots showed that they were also induced by mechanical wounding, ZnSO 4 , abscisic acid, and salicylic acid treatments with variable expression levels ( Figure 7B-E).…”
Section: Discussionsupporting
confidence: 52%
“…In recent years, a novel class of NAC proteins with a highly conserved NAC domain (for NAM, ATAF1/2, CUC2) (Aida et al, 1997) was identified. The proteins were recognized as transcription factors (Fujita et al, 2004;Tran et al, 2004) that participated in the formation of embryos (Duval et al, 2002), leaf senescence (Guo and Gan, 2006;Uauy et al, 2006), flower organ development (Sablowski and Meyerowitz, 1998), fruit development and senescence (Liu et al, 2009), cell cycle control (Kim et al, 2006), seed development , secondary-wall formation (Mitsuda et al, 2007;Mitsuda and Ohme-Takagi, 2008), hormone signaling (Fujita et al, 2004;Jensen et al, 2008), responses to pathogens and insect feeding (Delessert et al, 2005;Jensen et al, 2007;Lin et al, 2007), as well as responses to different abiotic stresses (Kim et al, 2007;Lu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, NAC proteins have been implicated in disease defense and abiotic stress signaling. Several NAC proteins have been shown to interact with virus proteins [19][20][21], or to play direct roles in regulating pathogen defense [22]. Some NAC proteins were recently identified as abiotic stress regulators.…”
Section: Introductionmentioning
confidence: 99%
“…The ataf1-1 mutant line showed decreased resistance to a biotrophic fungus as a consequence of increased ABA level [22,31]. ATAF1 was also reported to be a negative regulator in drought response based on analysis of ataf1 mutants [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among the three members, after which this family is named, NAM (No Apical Meristem) from petunia is important for shoot apical meristem formation (Souer et al, 1996), CUC2 (cup-shaped cotyledon) is involved in controlling the formation of boundary cells of the meristem (Aida et al, 1997), and ATAF1, 2 show dual function in biotic and abiotic stress responses (Collinge and Boller, 2001;Delessert et al, 2005;Jensen et al, 2007;Lu et al, 2007;Jensen et al, 2008;Wang et al, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%